How do TV and radio hosts speak? Vowel tenseness as an index of formal and serious speaking style - Čičirkaitė, Ramune (Taikomoji kalbotyra, 2022)
The present paper reports the instrumental analysis of the unstressed variants of /iː/, /uː/, /eː/, /oː/, /æː/ and /ɑː/. The study was carried out by employing the sound analysis software PRAAT, which was used to measure the length and tenseness of the specified variants. 10 residents of Vilnius city and 10 hosts of TV/radio programmes covering serious public topics were selected as the informants of the study. The main aims of this research were as follows: (1) to determine whether vowel length and tenseness differentiate the pronunciation of Vilnius city residents from that of the hosts of TV/radio programmes covering serious public topics, and (2) to reveal whether the hosts of TV/radio programmes use the length or tenseness of the unstressed variants of /iː/, /uː/, /eː/, /oː/, /æː/, /ɑː/ as a resource for creating a formal and serious speaking style. The current study examines, among other things, if the TV/radio hosts pronounce the unstressed variants of /iː/, /uː/, /eː/, /oː/, /æː/, /ɑː/ systematically more tensely, or perhaps on the contrary – they create the impression of a serious style only with isolated sounds of increased tenseness. The analysis has revealed that the hosts of TV/radio programmes covering serious topics pronounce the unstressed variants of /iː/, /uː/, /eː/, /oː/, /æː/ and /ɑː/ in the same length as Vilnius city residents speaking in a semi-formal style. Hence, vowel length in the said programmes is not a significant linguistic resource when creating a serious and formal speaking style and constructing the linguistic identity of a TV/radio host addressing serious public topics. However, TV/radio hosts covering serious public topics pronounce the unstressed variants of /iː/, /uː/, /eː/, /oː/, /æː/ and /ɑː/ with more tenseness than Vilnius city residents, which suggests that the style of the hosts is distinct from the semi-formal speaking style of Vilnius city residents and serves as a well-defined marker of a certain language standard. These findings are in line with some previous studies indicating that vowel tenseness statistically significantly distinguishes programmes covering serious public topics from entertainment-based programmes covering personal topics. Therefore, it can be argued that vowel tenseness differentiates speakers (TV/radio hosts vs. Vilnius city residents), types of programmes (programmes covering serious public topics vs. entertainment-based programmes covering personal topics), styles (formal vs. semi-formal), and language varieties (actual standard language vs. Vilnius speech). Thus, in the speech of hosts of TV/radio programmes covering serious public topics, tenseness acquires the indexical meaning of “I am speaking seriously”. The use of isolated vowels of increased tenseness is thus sufficient to create the impression of a serious speaking style and to form the linguistic identity of a TV/radio host covering serious topics.
Keywords: vowel length; vowel tenseness; indexical meaning; serious speaking style; standard language; stylization